2018
DOI: 10.1002/hpm.2612
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the doctor deficit on hospital management in Poland: A mixed‐method study

Abstract: In Poland, the long-term neglect of health workforce planning at the system level (there is neither a dedicated structure nor a formal strategy) has contributed to the current doctor deficit crisis. From the hospital managers' perspective, who are on the frontline of the problem impact, urgent solutions are needed that would at least alleviate its scale in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Still, statistically significant differences in the hospital financial performance were identified. Currently in Poland, local (county and/or city-county) hospitals are facing major challenges related to both the level of financing as well as doctor deficits [39,40]. In 2018, the majority of county hospitals generated a gross loss (55.3%) while almost half of units had overdue liabilities (48.5%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, statistically significant differences in the hospital financial performance were identified. Currently in Poland, local (county and/or city-county) hospitals are facing major challenges related to both the level of financing as well as doctor deficits [39,40]. In 2018, the majority of county hospitals generated a gross loss (55.3%) while almost half of units had overdue liabilities (48.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, while assessing hospitals' financial performance, the national health policy context must be carefully analyzed. In Poland, numerous previous analyses indicated that there is no single, leading cause of public hospitals' poor financial standing and debt problem [18][19][20][21][22]39]. Instead there is a mix of both macro-and micro-level factors that contribute to undermining public hospitals' financial standing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these policies effectively prevented the spread of the epidemic and slowed the spread of a number of infectious diseases. Furthermore, the need for tele-medicine services became more important to reduce the movement of patients (17). Therefore, doctors worldwide were encouraged to use the hospital cloud system to provide simple medical advice and treatment recommendations (18).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements in Information and Communication Technology (ICT) have paved the way toward new innovative tele-healthcare services able to face the growing demand of even more accessible medical treatments [1,2]. Moreover, in the pandemic condition such as that we are living at the time of writing of this paper due to the Covid-19 virus, the need of tele-healthcare service becomes dramatically fundamental to reduce the movement of patients, thence reducing the risk of infection.…”
Section: Introductionmentioning
confidence: 99%